Enhancing Students' Science Process Skills Through Design Worksheet-Based Inquiry Integrated PhET Simulation on Acid and Base Material - Buhera*, Rusdiman; Ayu, Sri Bona; Nurohman, Sabar (Jurnal IPA & Pembelajaran IPA, 2024)
Integrating PhET on inquiry-based worksheets can foster a more interactive and hands-on learning environment that encourages active student participation throughout the educational process. The research aims to develop an integrated inquiry-based worksheet PhET simulation. This research type is RD, using the 4-D model, which designs learning activities to enhance science process skills. The validators totaled four people, including media experts, content experts, and two practitioners. The readability test uses ten for 9th-grade students. The research findings indicate that the worksheets created have a very high average validity, with an Aiken V value of 0.97. The readability test results were obtained with an average readability percentage of 96% in the very good category and without revision. The effectiveness of the worksheets developed to improve science process skills obtained an N-gain of 0.71 in the high category. This means that PhET simulation integrated inquiry-based worksheets are feasible, practical, and effective for science learning to improve science process skills